Strategi Penyesuaian Draft Heater terhadap Konsumsi Fuel Oil dan Emisi Gas Buang pada Heater - Wendri Eko Nopri; Ratni Dewi; Ridwan Ridwan (Politeknik Negeri Lhokseumawe, 2026)
Optimization of combustion systems in industrial heaters is essential to improve energy efficiency and reduce flue gas emissions. This study aims to analyze the effect of draft heater adjustment on fuel oil consumption and exhaust gas emissions in Heater. The method employed was a field experimental approach using a comparative analysis before and after optimization, through gradual reduction of damper opening and closure of air registers on inactive burners. Observed parameters included fuel oil consumption, excess O₂ levels, stack temperature, heater efficiency, and exhaust gas emissions. The results show that draft optimization significantly reduced fuel oil consumption from 1.1868 m³/h to 0.7345 m³/h, equivalent to a reduction of 38.1%. Heater efficiency increased from 67.35% to 72.26%, influenced by a decrease in excess air from 10.19% to 7.09% and a reduction in stack temperature from 253.5°C to 222.8°C. Furthermore, emissions of CO₂, NOx, and SOx were significantly reduced due to improved combustion quality and lower fuel consumption. This study concludes that draft heater adjustment through damper control and air register optimization is an effective strategy to simultaneously enhance energy efficiency and reduce emissions without requiring major equipment modifications. The findings are expected to serve as a practical reference for improving the performance and environmental sustainability of industrial heater operations..